Caffeic Acid Inhibits NFkappaB Activation of Osteoclastogenesis Signaling Pathway - Ferry Sandra; Toshio Kukita; Quan Yong Tang; Tadahiko Iijima (The Prodia Education and Research Institute (PERI), 2011)
BACKGROUND: Caffeic acid (3,4-dihydroxycinnamic acids) is involved in various green plants. Based on our previous report, a major component of sweet potato extracts, possibly caffeic acid, was shown as a promising inhibitor of osteoclastogenesis. However, the effect of caffeic acid in inhibiting osteoclastogenesis needs to be confirmed. The underlying mechanism needs to be disclosed as well.METHODS: Caffeic acid in various concentrations was added to in vitro osteoclastogenesis of receptor activator nuclear factor kB ligand (RANKL)-tumor necrosis factor alpha (TNF-α)-macrophage colony stimulating factor (M-CSF)-induced bone marrow-derived monocyte/macrophage precursor cells (BMMs) and RANKL-TNF-α-induced RAW264 cells D-Clone (RAW-D cells). Tartrate resistant acid phosphatase (TRAP) staining was performed and TRAP-positive polynucleated cells (PNCs) were counted. For apoptosis analysis, caffeic acid-treated BMMs, RAW-D cells and osteoclast-like PNCs were subjected to Sub-G1 Apoptosis and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assays. To measure NFkB activity, RAW-D cells were transfected with pNFkB-TA-Luc and subjected to Dual Luciferase Reporter Assay System.RESULTS: Caffeic acid inhibited osteoclastogenesis of RANKL-TNF-α-M-CSF-induced BMMs as well as RANKL-TNF-α-induced RAW-D cells in a dose dependent manner. Caffeic acid did not induce apoptosis in BMMs, RAW-D cells and osteoclast-like PNCs. RANKL-TNF-α-induced NFkB activity in RAW-D was diminished by caffeic acid in a dose dependent manner. Significant NFkB activity inhibtion was observed starting from 1 µg/mL caffeic acid. CONCLUSIONS: Caffeic acid could be a potent osteoclastogenesis inhibitor through inhibition of NFkB activity. Our present study should be further followed up to disclose caffeic acid's possible overlying signaling pathways in inhibiting osteoclastogenesis.KEYWORDS: caffeic acid, osteoclastogenesis, NFkB, RANKL, TNF-α